Metodología de implementación de un sistema integrado de gestión de las normas ISO 9001 e ISO 30301 para mejorar el desempeño del sector notarial (2018)
In the international context, the implementation of different management systems is of great relevance for many organizations, since it offers them the opportunity to improve their overall performance in response to the great challenges generated by the environment. However, from the literature it is pointed out that there is still a great difficulty for organizations to manage several management systems separately, as well as to carry out the integration of several of them, because in the academic community there is still no consensus on the most effective way to do it. Therefore, an innovative methodology for the implementation of an integrated management system for ISO 9001 and ISO 30301 standards is proposed to improve the performance of the notarial sector, from the analysis of integration models, success cases, failure and abandonment of management systems. The study was carried out in a notary office in the department of Cundinamarca, through the analysis of qualitative and quantitative variables. The qualitative variables are examined with a perception questionnaire, addressed to the staff during the application of the implementation methodology; the results highlight the care of their organizational model; reduction of redundancies and duplicities in the administration of the different management systems; the establishment of effective processes for the creation and control of documents; finally, obtaining objective performance metrics. The quantitative variables after the implementation of the integrated management system, highlight improvements in performance over process times, resources and costs. During the development of the methodology, common elements of the sector are identified to affirm their compatibility with any notary according to Colombian legislation.